A imagem esfacelada do professor: um estudo em textos de revistas - Buttler, Daniella Barbosa (2009)
In this research we investigated the reconfigurations constructed in texts about teachers and their work produced by chronicle writers and journalists from Veja São Paulo and Nova Escola magazines. In order to do that, we checked the characteristics of the teacher s actions, in their work situation, which were constructed in some of the texts that are distributed in different realms and to different target readers. Through this checking we identified some linguistic-discursive forms which allow us to detect such reconfigurations. The choice of these two media supports is justified because we have, on the one hand, Veja São Paulo magazine, which target the general public and is read in the largest city in Brazil, and on the other hand, Revista Nova Escola, which is destined exclusively to educators and is read throughout the whole country. Thus, we could verify if there are similarities and/or differences between the reconfigurations of the teacher s actions that are constructed in these magazines, according to the context of their production. The decision to concentrate on the chronicle genre is justified by the fact that it deals with themes that are tied up to daily life, in a more literary and subjective stile than other kinds of genres and it has levels of textuality. The period of time chosen, from 2000 to 2006, is justified because in the early 21st century one can hear the echoes from the National Curriculum Parameters (PCNs) which were launched in the last decade of 20th century and led to deep changes in the history of Brazilian education. Overall, the procedures used in the research come, especially, from the sociodiscursive interactionism as per the LAF Group (Bronckart, 2004) and the ALTER group (Machado, 2004 and 2005), besides other authors whose concepts are compatible with our theoretical frame for the interpretation of texts. These authors include Amigues (2002), Saujat (2002), Faïta (2002) and Clot (2004b). Amongst these procedures, we take as reference for data analysis, the socio-interactional production context, the organizational level, especially the general textual plan and the types of discourse; the enunciative level, focusing on voices and modalizations, and, finally, the semantic level, adopting as analysis categories the constituent elements of action as per the model projected by Bronckart (1997 et seq.) and reviewed by Machado (2009/in print). The results of analysis of the texts from Revista Nova Escola were divided in two parts: the chronicles and the scripts. The chronicles showed that the teacher of the past, valued for his patience, understanding, goodness and tenderness is missed, and, because they were like that, they could act. On the other hand, the reflection scripts revealed a speaker who addresses the teacher as if s/he did not know how to act, by dictating prescriptions, with verbs in the imperative on how to discuss the career and how to teach, without disguising the prescriptive character; and by taking the teacher from ancient times as model, disregarding social-historical conditions. As for the results of analysis of the texts from Veja São Paulo magazine, we found a counterpoint and a confrontation between the teachers from the past and the teachers of the present: according to these reconfigurations, the former ones demanded and acted, while the latter ones present themselves as impotent to act, due to changing in roles and in the relationship between teacher and students, parents and school direction. We notice then that the chronicles from Revista Nova Escola reconfigure the teacher as if s/he were in a distant past, whose social conditions for working were totally different. Even though, as we can see in the scripts, this magazine presents this teacher as being ideal for nowadays while the chronicles from Veja São Paulo magazine show the teachers as they currently are, with their multiple real problems which make their traditional role oscillate